Graph Algorithms and Applications 1. - Tamassia, Roberto (World Scientific Publishing Company, 2002)
This book contains volumes 1-3 of the Journal of Graph Algorithms and Applications (JGAA) . Topics of interest include design and analysis of graph algorithms, experiences with graph algorithms, and applications of graph algorithms. JGAA is supported by distinguished advisory and editorial boards, has high scientific standards, and takes advantage of current electronic document technology. The electronic version of JGAA is available on the Web at http://www.cs.brown.edu/publications/jgaa/. Contents: Volume 1: 2-Layer Straightline Crossing Minimization: Performance of Exact and Heuristic Algori.